(untitled) (UNWE Yearbook, 2020)
In this text we identify the current professional profile of those employed in the communications sector – journalists, PR experts and advertisers. The main argument is that the introduction of technology leads to a redefinition of communicators’ expertise and the emergence of specific new professional roles. There are major transformations going on in each of the professions – new professional roles and requirements appear that demand advanced competences, which we have examined from the point of view of technological competencies, digital content competencies and strategic competencies. Our documentary and content analysis of open positions in global job offering and finding websites has shown that in the communication professions there is a convergence of professional expertise and at the same time preserving the professional identity. The presence of convergent competencies does not result in a blurring of the boundaries between the different communication sectors, but elevates those sectors to a new level of technological narrative, without depersonalizing their autonomy and social role. The research shows the growing tendencies regarding the digital content, concretises the new professional communication roles and highlights the expertise requirements of the business sector.